KARAKTERISTIK FISIK DAN TINGKAT BAHAYA EROSI TANAH ULTISOL - sudaryono, Sudaryono (BPPT)
Soil erosion is a major factor leading to cause land damage in the upstream region. Therefore, erosion control should be done in the preservation of land resources and the environment can be maintained and the welfare of farmers can be improved. Land Ultisol widespread in many Kalimatan Islands, ultisol soil types other than guilty of fertility, soil types have the property ultisol easy erosion. As a result of coal mining activities carried out by PT KPC lead to peeling layers of top soil to the depth of rock. This stripping has directly changed the soil condition. Ultisol soil physical conditions in Kalimanan (available water capacity, density lumps, texture, structure, pore space and permeability of the soil) are relatively low, so they need to improve theaddition of organic materials, and lime. The process of reclamation of former coal mining PT. KPC has been done very well. The analysis of fertility levels and the amount of potential soil erosion occurs indicates that the post-miningrehabilitation revegetation way to post-mining land with the procedure referred. It can be seen from the parameters of soil fertility and erosion rates of post-mining land have been rehabilitated (56.5614 erosion rates tons/hectare/year) with areas of pristine forests (erosion rates 52.175 tons/hectare/year) were not show significant changes.Keywords: ultisol, rehabilitation, physical soil, erosion